Dimensionamento e comparativo entre estacas Franki, hélice contínua e Strauss: estudo de caso - Gehlen, Douglas Dalton (2016)
Foundations are structures responsible for receiving the loads of the superstructure and transmitting them to the ground. The objective of this work is to size and compare foundations in Franki, Continuous Propeller and Strauss stakes for a building located in the city of Pato Branco, PR, indicating in the end the most technically and economically viable solution. The work carried out a bibliographical research on foundations, borings and soils, dimensioned the stakes geometrically, promoted the sizing of the blocks through software, and elaborated the budget for the different solutions. At the end, the comparative study was performed analyzing costs, executive schedules, construction processes, and equipment mobilization. It was verified, through the comparative realized that, for the conditions of this project, the cuttings type Franki are the most viable option technically and economically. Through the work carried out, it was possible to establish a calculation route for deep foundations, as well as to determine the best alternative for the building under study.